A Tibetan revolutionary : the political life and times of Bapa Phüntso Wangye - Goldstein, Melvyn C. (University of California Press, 2004)
This is the as-told-to political autobiography of Phüntso Wangye, one of the most important Tibetan revolutionary figures of the 20th century.